Prevention Focus Relates to Performance on a Loss-Framed Inhibitory Control Task - Files, Benjamin T.; Pollard, Kimberly A.; Oiknine, Ashley H.; Passaro, Antony D.; Khooshabeh, Peter (Frontiers in Psychology, 2019)
Information framing can be critical to the impact of information and can affect individuals differently. One contributing factor is a person's regulatory focus, which describes their focus on achieving gains vs. avoiding losses. We hypothesized that alignment between individual regulatory focus and the framing of performance feedback as either gain or loss would enhance performance improvements from computer-based training. We measured participants’ (N=93) trait-level regulatory focus; they then trained in a go/no-go inhibitory control task with feedback framed as gains, losses, or control feedback conditions. Some changes in performance with training (correct rejection rate and response time) were consistent with regulatory fit, but only in the loss-framed condition. This suggests that regulatory fit is more complex than cursory categorization of trait regulatory focus and feedback framing might indicate. Regulatory fit, feedback framing, and task affordances should be considered when designing feedback or including game-like feedback elements to aid computer-based training.